Identifikasi Jenis Dan Persentase Biaya Non Product Output (NPO), Efisiensi Produksi Melalui Penerapan Eko-Efisiensi Pada Produksi Tahu Tradisional di Desa Banyuraden, Kecamatan Gamping Kabupaten Sleman - Joko Susilo (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
One of efficiency indicators is Non Product Output (NPO) management. NPO was all of material, energy, and water used for production process but not part of the product. NPO concept gives us a different description to measure efficiency potential. In some food products, there are significant reduce of NPO cost and NPO cost percentage toward the total production cost of chicken-based foods in street food with maintaining food quality along with production efficiency. The research aims to create the NPO identification, controlling, and monitoring form as the implementation of short-term eco efficiency and NPO type identification, comparison of NPO cost percentage to total production cost and also information of production efficiency for the Traditional Tofu Production (TFP). This research used Pretest-post test group design in three vendors. The Eco efficiency form applied to the 3 vendors for 2 replication productions and for a month. The treatment of eco efficiensy by NPO Identification, controlling, and monitoring form and compeleted by Production Guideline Booklet. Data which were measured and observed were the production input identification and NPO (materials, energy, water), three groups of NPO (that cannot be avoided, can be avoided and can be saved), total production cost, % NPO cost to total production cost and production efficiency. The data were analyzed descriptively. NPO identification, contolling, and monitoring format has been designed for Traditional Toufu Production (TFP) or home industry as the eco efficiency process. Totally, there was decreasing of NPO types from 17 to 11 types (35% decreasing). The treatment had decreased NPO total volume from 49 to 22 volume (55% decreasing). There was decreasing for percentage of NPO cost from 48% to 36% (11,50% decreasing). For the 3 groups of NPO, the avoided NPO contributed by 11,30% decreasing of percentage of NPO cost, and this was the highest contributoin of decreasing percentage NPO cost than the unavoidable NPO and the unvoided-efficient NPO. There was the 15,23% production efficiency. Application of Eco Efficiency through identification, controlling and monitoring NPO in Traditional Tofu Production (TFP) can decrease NPO types, NPO volume, and percentage of NPO cost toward total cost. Application of Eco Efficiency can increase production efficiency of Traditional Tofu Production.